Respuesta :
When [tex]x=3[/tex], we get the parabola
[tex]z=-4-2y^2[/tex]
We can parameterize this parabola by
[tex]\vec r(t)=(3,t,-4-2t^2)[/tex]
Then the tangent vector to this parabola is
[tex]\vec T(t)=\dfrac{\mathrm d\vec r(t)}{\mathrm dt}=(0,1,-4t)[/tex]
We get the point (3, 2, -12) when [tex]t=2[/tex], for which the tangent vector is
[tex]\vec T(2)=(0,1,-8)[/tex]
Then the line tangent to the parabola at [tex]t=2[/tex] passing through the point (3, 2, -12) has vector equation
[tex]\ell(t)=(3,2,-12)+t(0,1,-8)=(3,2+t,-12-8t)[/tex]
which in parametric form is
[tex]\begin{cases}x(t)=3\\y(t)=2+t\\z(t)=-12-8t\end{cases}[/tex]
for [tex]t\in\Bbb R[/tex].
The parametric equation of the tangent line is [tex]L(t)=(3,2+t,-12-8t)[/tex]
Parabola :
The equation of Paraboloid is,
[tex]z =8-x-x^{2} -2y^{2}[/tex]
Equation of parabola when [tex]x = 3[/tex] is,
[tex]z=8-3-3^{2} -2y^{2} \\\\z=-4-2y^{2}[/tex]
The parametric equation of parabola will be,
[tex]r(t)=(3,t,-4-2t^{2} )[/tex]
Now, we have to find Tangent vector to this parabola is,
[tex]T(t)=\frac{dr(t)}{dt}=(0,1,-4t)[/tex]
We get, the point [tex](3, 2, -12)[/tex] when [tex]t=2[/tex]
The tangent vector will be,
[tex]T(2)=(0,1,-8)[/tex]
So that, the tangent line to this parabola at the point (3, 2, −12) will be,
[tex]L(t)=(3,2,-12)+t(0,1,-8)\\\\L(t)=(3,2+t,-12-8t)[/tex]
Learn more about the Parametric equation here:
https://brainly.com/question/21845570